Moral barriers to birth control access: How the pill changed Dutch women's lives - When religion did not get in the way - Olivier Marie; Esmée S. Zwiers (Tinbergen Institute, 2021)
We investigate how religious beliefs affected the take up of the birth control pill and impacted women's outcomes using the 1970 liberalization of oral contraceptives in the Netherlands. We first document a massive and immediate drop in fertility among minor women, aged 21 or younger, for whom access restrictions were most drastically lifted. We then evaluate how area level social norms - as proxied by votes for religiously opposed political parties - influenced pill adoption by examining its impact on female fertility control and human capital formation. We find that younger women who grew up in more liberal areas were much less likely to experience a birth or marriage as a minor, invested more in education, and ended up in wealthier households. Finally, we study the potential additional impact of supply side frictions stemming from the moral views of the gatekeepers to the new birth control technology. We show that a larger proportion of religiously opposed health professionals - GPs and pharmacists - around a woman at the time of liberalization cancels out the short- and long-run benefits from pill access.
Keywords: I18; J12; J13; Z12; 330; birth control; fertility; marriage; human capital; religion; the Netherlands